A winter dream - Evans, Richard Paul (Simon & Schuster, 2012)
A holiday tale inspired by the biblical story of Joseph and the coat of many colors follows the modern story of Joe, who after being forced out of the family business by jealous siblings becomes the chief advisor to the CEO of another company and his own family's savior in the face of a troubled economy.